Effects of Gender and Academic-Risk Behavior on the Career Maturity of Rural Youth - Jay W. Rojewski; Robert C. Wicklein; John W. Schell (Journal of Research in Rural Education, 1995)
We exd-minedthe impact of gender and academic-risk behavior on the career maturity attitudes and competence of rural adolescents. Using the Career Maturity Inventory (Crites, 1978), a two-way multivariate analysis of variance (MANOVA) found significant main effects for gender and academic-risk status on affective career maturity. A separate two-way MANOVA focusing on career maturity competence found significant main effects for academic-risk status. The career development problems of rural adolescents identified as academically at-risk highlight a need for targeted secondary career education and vocational preparation programs. However, to maximize the effectiveness ofvocational programsfor these rural youth, greater attention must be paid to the career development issues they experience.